Performance Shaping Factors of Railway Train Operation Human-Caused Accidents: An Interpretive Structural Modelling Approach - Guobao Zhang, Qi Wang (Design Engineering, 2020)
As human-caused accident is one of the main accidents in railway traffic, the key influencing factors of human factors in railway traffic accidents is revealed in this paper by analyzing the performance shaping factors of the traffic personnel, so as to improve the safety of railway traffic and reduce the incidence of human-caused accidents. Firstly, a mechanism model of railway human-caused accidents is established based on the theory of railway HRA, then a set of performance shaping factors for railway train operators is constructed, and finally an interpretive structural model of railway human-caused accidents is established by using ISM method. The research results show that work experience, personal expectations, context awareness, attention distribution, work load, fatigued operation and competence are the direct influence factors, and operation instruction, training system, human-machine interface, teamwork, information communication, supervision system and operating environment are the indirect factors of PSFs of railway human-caused accidents, and safety culture is the most fundamental factor that causes human-caused accidents in railway. It is of great significance to explore the influence mechanism of various factors on railway human-caused accidents, strengthen the identification and regulation of the PSFs and improve railway traffic safety by dividing the multi-level hierarchical structure of PSFs of railway human-caused accidents.